IN SILICO STUDY OF SOYBEAN (Glycine max L.) ISOFLAVONES FOR ANTI-BREAST CANCER THROUGH HER2 TARGETING - Ayu Tri Agustin; Nadia Khairun Nisa; IGA Karnasih; Mohammad Rofik Usman; Shinta Mayasari (Indonesian Pharmacopeia Journal, 2025)
One of the cancers with the most excellent death rates worldwide, including in Indonesia, is breast cancer. Elevated HER2 expression significantly contributes to breast cancer progression by stimulating cell proliferation. Targeted therapies such as trastuzumab have limitations due to potential side effects. This study aims to identify the possible role of soybean (Glycine max L.) isoflavone compounds in inhibiting HER2 using an in silico approach prediction of physicochemical properties, pharmacokinetics, and bioactivity through SwissADME and PASS Online. The Hex 8.0.0 docking tool and Biovia Discovery Studio 2019 looked into how molecules interact with each other in complicated ways. Our study revealed that physicochemically the compounds acetylgenistin, acetylglycitin, and acetyldaidzin met Lipinski's Rule of Five criteria (BM (< 500), Log P (< 5), HBD (< 5), HBA (< 10), and MR (40-130)), pharmacokinetically the compound acetylgenistin met the ADME parameters and bioactively all six compounds had anticancer activity (Pa > 0.2). Based on the results of molecular docking analysis, the six soy isoflavone compounds can interact and have low binding energy values. The binding energy values of malonylgenistin, acetylgenistin, and acetyldaidzin are the lowest and close to trastuzumab, at -286.6, -283.4, and -277.7kcal/mol, respectively. These findings suggest that soybean (Glycine max L.) isoflavone compounds have potential as anticancer drug candidates in inhibiting HER2.